Age at first sex: understanding recent trends in African demographic surveys. (30th November 2004) - Zaba, B; Pisani, E; Slaymaker, E; Boerma, J Ties
Abstract : Objectives: To describe recent trends in age at first sex in African countries, identifying and making due allowances for a variety of common reporting errors. Methods: Demographic and Health Surveys (DHS) data from six African countries conducting three or more surveys since 1985 were analysed using survival analysis techniques, combining information on virginity status and retrospective reporting of age at first sex. Hazard analysis was used to separate the effects of reporting error and compositional change and to estimate true changes in sexual debut over time. A multistate life table analysis incorporating transition to first marriage allowed cohorts to be classified according to person years spent as virgins, as sexually active unmarried, and married. Results: Intersurvey comparisons generally suggested a slow secular rise in age at first sex. However, tracing birth cohorts between surveys revealed inconsistencies—median ages reported by female members of a birth cohort in their teens were generally higher than those reported when they reached their twenties, even when allowing for residence and education changes—probably a result of young, sexually active women denying they had ever had sex. Male birth cohorts tend to display the opposite kind of bias. Conclusions: Uganda, Kenya, and Ghana have experienced a more pronounced and unambiguous decline in premarital sexual activity than Tanzania, Zambia, and Zimbabwe, with statistically significant increases in age at first sex. In addition, Uganda has maintained a very short interval between onset of sexual activity and marriage for both sexes.